ARTIFICIAL INTELLIGENCE IN EDUCATION: PEDAGOGICAL PERSPECTIVES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the pedagogical aspects of using artificial intelligence (AI) technologies in the educational process. The study highlights the role of AI tools in developing learner-centered education, enhancing teaching effectiveness, and activating students  ’cognitive activity. In addition, the advantages and pedagogical potential of AI-based educational systems, as well as the challenges that arise in the process of their implementation, are examined. The findings of the article are of significant importance for the application of innovative approaches in modern pedagogical practice.